Implicações na subjetividade de usuários do programa de proteção às vítimas e testemunhas ameaçadas advindas da alteração do nome - RODRIGUES, Cinthia Maria Urbano (2016)
This study aimed to discuss the subjective implications arising from the change of name users of the Program to Protect Victims and Threatened Witnesses. Initially presents the historical and social context that led to the Protection Program for Witnesses highlighting the particularities of this Brazilian experience that differentiates the program from other countries, constituting from impasses and contradictions as human rights policy. Regards the theoretical basis, it sought the literature review, subsidies on environment protection policy, human rights, violence and impunity, from the survey produced research on PROVITA even as information in documents guide the program were privileged. Regarding the methodology used, prioritized reports highlight the experiences recorded in a field diary the author of this work, and research of other scholars who express the concerns and suffering of subjects inserted in the program. It is also considering the theories that guide the Program document that guides the practice of the psychologist in this policy, we sought theoretical and methodological foundations of Socio-Historical Psychology, which conceives this study, the notion of the subject, from the categories: subjectivity and identity. It is noteworthy that it was necessary to use a dialogue with the concept of the subject and name as understanding of psychoanalysis, given that the latter category greatly emphasizes the importance of what is beyond the civil name as Jacques Lacan. We conclude that the program stands out as its objective to preserve the physical integrity of protected persons and the perspective of social reintegration. However, the means of promoting citizenship and autonomy of these individuals still need many initiatives, among them, dialogue and compromise between the other social policies to guarantee a more refractory to experience hudles and difficulties inherent in that policy. Thus, while we do not see the viability of this reality, then it reinforces the importance of the program to direct special attention to the size of the subjectivity of his witnesses, valuing it even more as a policy that protects lives.